Pengaruh Etos Kerja Dan Kemampuan Kerja Terhadap Kinerja Pegawai Perumda Air Minum Wair Pu’an Kabupaten Sikka - Maria Rislianty Nona Rit; Antonius Philippus Kurniawan; Yustina Olivia Da Silva (Jurnal CUAN Universitas Nusa Nipa Maumere, 2023)
The background of this research is the result of a pre-survey wich showed that the employee performance in Wair Pu’an Regional Water Supply Company has not been maximized. This research aimed to; (1) know the description of employee perfomance, work, ethic, and workability; (2) analyze the effect of work etich and workability on employe performance etther partially or simultaneously. The population of the study were employees of Perumda Wair Pu’an Sikka Regency as many as 50 employees. Since the population is limited, this research was carried out by census or saturated sampling. Data were collected through qestionnaires and analyzed using descriptive methods and inferential statistics, namely multiple linear regressions. Hypothesis testing is done through the F-test and t-test. The results of the descriptive analysis showed that the employee performance, work etich, and workability variables were good enough. The result of the t-test showed that the variables of work etich and workability had a significant value on employee perfomance. The result of the f-test showed that the variables of work ethic and workability simultaneously had a significant effect on employee perfomance. The coefficient of determination was 0,523, wich means that the contribution of work ethic and workability variabels to employee perfomance was 27,3%